APLIKASI ERROR CORRECTION MECHANISM DALAM ANALISIS DAMPAK PERTUMBUHAN EKONOMI, KONSUMSI ENERGI DAN PERDAGANGAN INTERNASIONAL TERHADAP EMISI CO2 DI INDONESIA - Fitri Kartiasih; Adi Setiawan (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2020)
Economic development is an effort to improve people's lives. However, economic development has negative externalities. Emissions generated from economic activities can pollute the environment. This study purpose to determine the relationship between economic growth and CO2 emissions based on the Environment Kuznets Curve (EKC) hypothesis and analyze the influence of energy use, economic growth and international trade on CO2 emissions in Indonesia in the period 1977-2014 using Error Correction Mechanism (ECM) analysis. The results showed that the EKC hypothesis does not apply in Indonesia, meaning that economic development carried out during the research period still pursues increased income without regard to environmental quality so that increased per capita income is accompanied by increase in CO2 emissions. Based on econometric analysis of ECM, it shows that the variables of energy use, economic growth and international trade have a statistically significant effect on CO2 emissions in Indonesia in the long run. In the short term, economic growth, and error correction terms have a statistically significant effect while the variables of energy consumption and international trade do not have a statistical effect on CO2 emissions in Indonesia.